2019
DOI: 10.1111/tpj.14330
|View full text |Cite
|
Sign up to set email alerts
|

A MYB/bHLH complex regulates tissue‐specific anthocyanin biosynthesis in the inner pericarp of red‐centered kiwifruit Actinidia chinensis cv. Hongyang

Abstract: These authors contributed equally to this work. SUMMARYMany Actinidia cultivars are characterized by anthocyanin accumulation, specifically in the inner pericarp, but the underlying regulatory mechanism remains elusive. Here we report two interacting transcription factors, AcMYB123 and AcbHLH42, that regulate tissue-specific anthocyanin biosynthesis in the inner pericarp of Actinidia chinensis cv. Hongyang. Through transcriptome profiling analysis we identified five MYB and three bHLH transcription factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
135
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(141 citation statements)
references
References 99 publications
(175 reference statements)
6
135
0
Order By: Relevance
“…In addition, it has been demonstrated that many transcription factors (TFs), including MYBs, NACs, basic helix-loop-helix (bHLH), WD40s, and WRKYs, are involved in the regulation of metabolic biosynthesis in plants and the regulatory pattern of these transcription factors is usually tissue-specific [43][44][45][46][47]. MYBs play a critical role in fruit and flower color formation via the regulation of structural genes in the flavonoid or anthocyanin biosynthetic pathway [43][44][45][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been demonstrated that many transcription factors (TFs), including MYBs, NACs, basic helix-loop-helix (bHLH), WD40s, and WRKYs, are involved in the regulation of metabolic biosynthesis in plants and the regulatory pattern of these transcription factors is usually tissue-specific [43][44][45][46][47]. MYBs play a critical role in fruit and flower color formation via the regulation of structural genes in the flavonoid or anthocyanin biosynthetic pathway [43][44][45][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GmMYB58 and GmMYB205 were demonstrated to be seed-specific activators for isoflavonoid biosynthesis in Glycine max [45]. Numerous reports have indicated that transcription factors from MYB, bHLH, and WD-repeat (WDR) families generally form a ternary complex (MBW complex), which coordinately activates or represses multiple genes in the regulatory network to influence metabolic biosynthesis [46,47,53,54]. Our study has identified a number of transcription factors including MYB, bHLH, and bZIP genes from vine tea (Additional file 11: Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…As an essential superfamily of TFs, bHLH proteins participate in regulating of a series of biological and developmental processes, such as flowering [19], root development [20], seed germination [21], anthocyanin or flavonoid metabolism [22][23][24], hormonal signaling regulation [25,26], as well as biotic and abiotic stresses responses [14,[27][28][29]. Under Fe deficiency stress, bHLHs have been shown to play a predominant regulatory role.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic mechanisms underlying anthocyanin accumulation have been repeatedly studied in many horticultural crops via transcriptome analysis (El-Sharkawy et al 2015;Cao et al 2018;Lin et al 2018;Bai et al 2017). Although transcriptomic studies were conducted on kiwifruit and kiwiberry, and some candidate genes were screened out (Li et al 2018a;Li et al 2018b;Li et al 2015b;Wang et al 2019;Peng et al 2019), these results were mainly based on limited numbers of anthocyanidin-related metabolites. Furthermore, pigmented kiwifruit and kiwiberry also showed distinct pigmentation patterns.…”
Section: Introductionmentioning
confidence: 99%